FOUNDATIONS OF DIAGNOSING AN INDIVIDUAL'S INTELLECTUAL AND CREATIVE GIFTEDNESS - Anatolii Palii (Vasyl Stefanyk Precarpathian National University, 2015)
The article argues for the urgency of research on an individual's intellectual and creative giftedness and emphasizes the theoretical, psychological, pedagogic, and socio-economic significance of the problem. It is claimed that the psychological practices in education may result in negative consequences through lack of high validity methods of diagnosing mental (intellectual and creative) giftedness. The selection of relevant psychodiagnostic procedures and methods of working with gifted individuals must be determined by a psychologically substantiated systemic theory of giftedness which is based on contemporary ideas of uniqueness and originality of the above-mentioned integral phenomena of the human psyche. The author provides a critical analysis of the psychometric (testometric) approach to diagnosing intellectual and creative giftedness (IQ index and creativity index). It is claimed that standardized tests are a priori unfit to objectively measure either the actual or the potential mental giftedness of an individual. The article explores the classifications of giftedness types in terms of quantitative criteria (indices), personality traits, occupations, motivation. The author questions the correctness of positing 'creativity' as an independent type of giftedness. It is argued that mental (intellectual and creative) giftedness is an inseparable structural and functional unity, a systemic attribute of psyche and is revealed as talents, personality traits and metacognitive experience in various activities. The author argues for the cognitive style approach to diagnosing mental giftedness. It is hypothesized that it can serve as a theoretical foundation for developing a systemic technique of diagnosing general giftedness, complies with the main principles of humanizing the educational space in Ukraine and is truly child-oriented, i.e. considers every individual's uniqueness and inimitability.